2001
DOI: 10.1046/j.1475-1313.2001.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular signs of systemic hypertension: A review

Abstract: Cardiovascular disease and stroke continue to be the chief causes of death in developed countries and one of the leading causes of visual impairment. The individual with systemic hypertension may remain asymptomatic for many years. Systemic mortality and morbidity are markedly higher for hypertensives than normotensives, but can be significantly reduced by early diagnosis and then efficient management. However, the ability of Optometrists to detect and appropriately refer systemic hypertensives remains general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
0
10
0
2
Order By: Relevance
“…The end arteriolar system of the retinal vasculature can be observed noninvasively and is particularly susceptible to chronic changes in blood pressure. As many people have their eyes examined every 1 to 2 years, optometrists should play an important public health role in screening for systemic hypertension, performing ocular fundus examination, measuring blood pressure, emphasizing the importance of regular general practitioner assessment, and referring suspect patients for appropriate management [37,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The end arteriolar system of the retinal vasculature can be observed noninvasively and is particularly susceptible to chronic changes in blood pressure. As many people have their eyes examined every 1 to 2 years, optometrists should play an important public health role in screening for systemic hypertension, performing ocular fundus examination, measuring blood pressure, emphasizing the importance of regular general practitioner assessment, and referring suspect patients for appropriate management [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, hypertensive retinopathy has been found to appear earlier than choroidopathy or optic neuropathy [16]. Ocular signs of systemic hypertension have been divided into those considered to be indicators of premalignant (early changes, prior to significant damage to the retinal vasculature) and malignant systemic hypertension [21,39]. …”
Section: Ocular Signs Of Systemic Hypertensionmentioning
confidence: 99%
“…Esto conlleva una pérdida de la capacidad de autorregulación, con dilatación de las arteriolas y pérdida de las uniones entre las células endoteliales y pericitos, con disrupción de la barrera hemato-retiniana, aumentando la permeabilidad de los vasos y extravasación de elementos formes sanguíneos a nivel intra-retiniano y superficial. En otros casos cuando la instauración de la HTA es de forma brusca no se producen fenóme-nos de adaptación por lo que se produce una rotura de todo el espesor de la pared del vaso dando lugar a hemorragias intraretinianas profundas 5,6 . Las hemorragias se clasifican en:…”
Section: Signos De La Retinopatía Hipertensiva Hemorragiasunclassified
“…En algunos casos son difíciles de observar al quedar ocultas por las alteraciones del epitelio pigmentario de retina o el edema retiniano difuso. Es importante señalar que cuando existen lesiones a nivel coroideo (coroidopatía hipertensiva) estamos ante un caso avanzado o maligno de la HTA que suele asociar insuficiencia renal [5][6][7] .…”
Section: Hemorragias Coroideasunclassified
“…For these reasons, some patients are not diagnosed with hypertension until after experiencing problems in visual acuity. If a referral is made on the presence of malignant hypertensive retinopathy, irreparable damage to the vascular system of the body as a whole has already occurred, thereby limiting treatment efficacy [16]. Thus, early detection of vasculopathy and, in turn, early disease management, presents the greatest potential for reducing morbidity and mortality associated with hypertension.…”
Section: Introductionmentioning
confidence: 99%